Noble metal sensitized invasive porous bioelectrodes: advanced medical device for enhanced neuronal activity and chronic alcohol treatment. Issue 71 (9th December 2020) - Kim, Hong Soo; Choi, Hansaem; Flores, Monica Claire; Razzaq, Abdul; Gwak, Young Seob; Ahn, Danbi; Kim, Mi Seon; Gurel, Ogan; Lee, Bong Hyo; In, Su-Il
Abstract : Novel metal sensitized invasive porous bioelectrodes ( x -IPB, x = Ag, Au, Pt) have high surface area and enhanced electrochemical properties, resulting in increased neural activity and alcohol detoxification. Abstract : Invasive bioelectrodes are widely used as an effective treatment for several acute and chronic diseases. In earlier work using high surface area invasive porous bioelectrodes evaluated in an animal model of alcoholism withdrawal, we demonstrated significantly improved electrophysiological and behavioral responses. In this study, we further modify the surface of these invasive porous bioelectrodes with noble metal (Ag, Au, Pt) nanoparticles. Compared to both conventional and porous bioelectrodes, noble metal sensitized invasive porous bioelectrodes show markedly increased low threshold (LT) and wide dynamic range (WDR) neuronal activity. In particular, Pt-sensitized invasive porous bioelectrodes show the highest WDR neuronal activity only upon insertion. In addition, Ag-sensitized invasive porous bioelectrodes, whose surface area is about 37 times greater than that of conventional bioelectrodes, show improved electrochemical properties with higher LT and WDR neuronal activity when stimulated. In an animal model of chronic alcoholism, using normal and alcohol-treated Sprague-Dawley (SD) rats evaluated with the elevated plus maze (EPM) test, the Ag-sensitized invasive porous bioelectrodes show about 20% higher open arms time. These results suggest that these noble metal-sensitized invasive bioelectrodes may offer improved therapeutic outcomes for the treatment of chronic alcoholism, and given these enhanced electrophysiological properties, for other conditions as well.